(untitled) (Discourse of Law and Administration, 2023)
The article aims to demonstrate the accuracy of the thesis that the regulation of customs and fiscal control in the Act on National Revenue Administration is flawed from the point of view of linguistic correctness and principles of lawmaking technique. Achieving this research goal requires the use of primarily linguistic and grammatical interpretation, which is basic for the dogmatic method in legal sciences, to analyse the source material. The findings made in this way were also confirmed by the conclusions drawn as a result of the method of legal semiotics. Names of legal terms should be created rationally and not cause information noise that hampers the legislator’s communication with the addressee of the legislation. However, customs and fiscal control nomenclature do not meet this standard.